Recent advancements in Point-of-Care Detection of Contaminants and Biomarkers in Human Breast Milk: A comprehensive review - Shruti Janakiraman; Rinky Sha; Naresh Kumar Mani (Sensors and Actuators Reports)
Breastmilk is an essential source of nutrients for newborn babies. It contains amino acids, nucleic acids and the essential immunological components required for the neonate to survive. Along with a number of other contaminants, it also includes several biomarkers, which are signs of a diseased state of the host. Thus, it is obvious that by examining the contents of this bodily fluid and how it affects the newborn, we can provide better healthcare solutions to both the mother and the child. There are several methods by which these analytes can be analysed, and they can be broadly classified in two categories; conventional and point-of-care based techniques. These approaches have benefits and drawbacks and are both in use today. However, point-of-care procedures are becoming increasingly popular in the scientific community because of their portability, affordability, and shorter turnaround times. In this review, the significance of employing these techniques to examine the intricacy of breastmilk as well as the contaminants and biomarkers that it contains will be covered. Wherever appropriate, the future of point-of-care approaches, including wearable sensors, has also been discussed, along with the significance, drawbacks, and advantages of combining these two technologies to recognize contaminants and biomarkers in breast milk.